Factors Facilitating and Impeding Women’s Retention in Math-Intensive STEM Fields - Almukhambetova, Ainur; Kuzhabekova, Aliya; Kim, Tatyana (Voprosy obrazovaniâ, 2025)
Increasingly, there has been a notable lack of female representation in math-intensive STEM fields, such as engineering, geosciences, mathematics, computer science, and physics. This issue persists despite the growing number of women graduating in STEM disciplines. Enhancing the number of women who complete their education and work in STEM sectors is a critical task. To address this issue effectively, it is crucial to understand the factors responsible for the underrepresentation of women, both among STEM students and within the workforce. This qualitative study explores the experiences of female undergraduate students enrolled in math-intensive STEM programs at universities to understand the factors contributing to the underrepresentation of women in STEM fields within the context of Kazakhstan. The analysis based on 29 interviews highlights a range of personal, distal, and proximal factors that may significantly influence the retention of women in math-intensive STEM fields. Furthermore, this article offers several recommendations to promote and support women’s involvement in STEM.